Validity and reliability of electroacoustic probe for diagnosis of developmental dysplasia of the hip - Nicolas Padilla-Raygoza; Georgina Olvera-Villanueva; Silvia del Carmen Delgado-Sandoval; Teodoro Cordova-Fraga; Modesto Antonio Sosa-Aquino; Vicente Beltran-Campos (BMC, 2017)
Abstract Background Sound transmission is used in the diagnosis of hip dysplasia since the end of the 80's. Aim of this study is to quantify the validity and reliability of electroacoustic probe for the diagnosis of hip dysplasia in neonates. Methods Diagnostic study included neonates aged 4-28 days, whose parents signed an informed consent. The probe was used three times for comparative sound transmission and with extension/flexion; hip ultrasound was performed with Graf technique as gold standard. Kappa was determined for intraobserver and interobserver reliability; validity was calculated with sensitivity, specificity, and predictive values. Results 100 neonates were included. For the comparative sound transmission, 0.80 and 0.81 Kappa were obtained for the intraobserver and interobserver respectively; with extension/flexion, Kappa 0.98 and 0.95 were obtained for the intraobserver and interobserver respectively. With comparative sound transmission, 44.8%, 97.7%, 76.5% and 91.3% for sensitivity, specificity, positive and negative predictive values, respectively; with extension/flexion test, the sensitivity, specificity, positive and negative predictive values: 82.8%, 99.4%, 96.0%, and 97.1%, respectively. Conclusion The electroacoustic probe is moderate valid and reliable for the diagnosis of developmental dysplasia of the hip. Trial registration Open Science framework https://osf.io/kpf5s/?view_only=0a9682c6w1c842ad8e1d9a66e8dcf038